Homeschooling: an Alternative Education in Indonesia - Achmad Razi (International Journal of Nusantara Islam, 2016)
This paper aims to examine homeschooling an alternative education in Indonesia. At the present time a lot of popping educational institutions, began formal education through non-formal education. The institute has a goal to educate the future generation. The result, not all educational institutions could be feasible for the education of children today, as in formal education. Often, formal education, structural, and impressed force, make students feel depressed, so they could not undergo the program learning with fun, excitement, and filled with love. Moreover, competition among learners causing some students feel stress so that the child is looking at learning as a liability burden and not as a requirement. In the present era, emerging institutions of alternative education in an effort to address the above issues, one of which is home schooling.